Journal of money, credit, and banking (Columbus Ohio State University Press, 1996)
The Journal of Money, Credit and Banking (JMCB), a leading professional journal read and referred to by scholars, researchers, and policymakers in the areas of money and banking, credit markets, regulation of financial institutions, international payments, portfolio management, and monetary and fiscal policy. The JMCB represents a wide spectrum of viewpoints and specializations in its fields through its advisory board, associate editors, and referees from academic, financial, and governmental institutions around the world.
The Journal of Money, Credit and Banking is published four times a year in February, May, August, and November Some issues are published in two parts Full text articles are availble on JSTOR: https://www.jstor.org/journal/jmonecredbank
Keywords: Money; MONEY; CREDIT; BANKING; FISCAL POLICY; FINANCIAL REGULATIONS; PERIODICALS